Separated [videorecording (DVD)] - Cartol, Gabriela (Greenwich, 2025)
Academy Awardʼ-winning filmmaker Errol Morris incisively probes the darkest chapter in recent American history: family separations. Merging narrative vignettes of one migrant family₂s plight with hard-hitting interviews with government officials, Morris paints a jaw-dropping picture of the state-sponsored crisis of cruelty, as over 1300 children remain separated today, according to the Department of Homeland Security.